The Bronze Age Necropolis at Ayia Paraskevi (Nicosia): Unpublished Tombs in the Cyprus Museum - Kromholz, Susan Foster
Ph.D. Dissertation; Anthropology, archaeology; Order No. 77-22, 816; p. 303 and p. 360: three cylinder seals from Tomb 6.